PENGARUH PERSON-JOB FIT DAN LINGKUNGAN PENGENALAN LAPANGAN PERSEKOLAHAN (PLP) TERHADAP PILIHAN KARIR MENJADI GURU - Sindyni Roffita; Meylia Elizabeth Ranu (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
An individual will consider various factors in their career choice. The aim of the research is to analyze the factors that dominantly influence career choices, namely person-job fit and the Introduction to Schooling Field (PLP) environment which simultaneously and partially influence the career choice of becoming a teacher for students in the 2020 Faculty of Economics and Business education study program at UNESA. Based on test results t obtained a significant value for the person-job fit variable of 0.000 and the PLP environment variable of 0.004 <0.05. Partially, person-job fit and the PLP environment influence the career choice of becoming a teacher. Meanwhile, the results of the F test obtained a significance value of 0.000, this shows that person-job fit and the PLP environment simultaneously influence the career choice of becoming a teacher for students in the FEB Unesa education study program. Apart from the t test and F test, an R Square value of 0.752 was obtained, which means that 75.2% of career choices to become a teacher were influenced by person-job fit and the PLP environment. Meanwhile, the remaining 24.8% is the influence of other variables not explained in this research.